Internet dan Pengaruhnya Terhadap Pengangguran di Indonesia Tahun 2015-2019 - Anna Kristiana Yunita (Future Science, 2021)
The internet has two effects, whether it supports or will it reduce productivity which will have an impact on the unemployment rate. This study aims to examine the effect of the internet on the unemployment rate in Indonesia in 2015-2019. Panel data analysis with the Feasible generalized least square (FGLS) method using STATA software was used to solve the problem of not fulfilling the assumptions of normality and heteroscedasticity in this study. Based on the results of data processing, the proportion of internet users shows a positive and statistically significant sign. The coefficient value of the proportion of internet users is 0.4898; which means that an increase in the proportion of internet users by 1 percent will cause the open unemployment rate to increase by 0.4898 percent, assuming the other variables are fixed. It can be concluded that the higher the proportion of internet users in an area, the higher the area's open unemployment rate. This is because the use of the internet in Indonesia is still not fully used to increase the productivity of the population such as looking for jobs or improving skills through training so that the internet actually causes the unemployment rate to increase.